Internal control and administrative management in the decentralized municipal Autonomous Government of the Pucará Canton - Piedra Vargas, Byron Patricio (2025)
In the global context, the evaluation of internal control is consolidated as an essential component in public administration, since it allows verifying the efficiency and effectiveness of operations, ensuring the reliability of records and guaranteeing compliance with relevant laws, rules and regulations. The main intention of this study was focused on determining the importance of internal control and administrative management in the decentralized municipal Autonomous Government of the Pucará Canton. The method used was a mixed type, with a descriptive analysis of secondary sources. The results showed that, although internal control is adequate, there are critical areas that need improvement, such as risk management and project supervision. The rating of the control system was 79 out of 100, highlighting good practices in control activities and organizational culture, but with weaknesses in the identification and management of risks